An analysis of flouting maxim in the Adam Project movie - Nabillah Holifatunnisa; Dyah Ambar Wuryandari (Lililacs Journal: English Literature, Language, and Cultural Studies Journal, 2023)
Language is used to communicate by humans with one another, not only in writing but also in the spoken form. Humans use language in spoken form to communicate. Sometimes the participants do not obey the Cooperative Principle. Some participant often gives more or less information, say something that glances at ambiguity, say something false and being irrelevant. This research focuses to find out the types of Flouting Maxim and the most Flouting Maxim frequently occurred found in The Adam Project movie. This research used descriptive qualitative method. In this research, the researcher used Grice’s (1975) theory in analysing the data. The data were taken from The Adam Project movie. The researcher found 30 data that contain Flouting Maxim in The Adam Project movie based on the theory. The result showed there are 4 types of Flouting Maxim namely Flouting Maxim of Quantity (4 data), Flouting Maxim of Quality (8 data), Flouting Maxim of Relation (4 data), Flouting Maxim of Manner (14 data). Meanwhile the most Flouting Maxim frequently occurred found in The AdamProject movie namely Flouting Maxim of Manner (14 data).